Analysis of Product Quality, Price and Service Quality on Customer Repurchase Intention at Marboba Outlet - Sagara, Deby; Muslih, Basthoumi; Soedjoko, Dodi Kusuma Hadi (Universitas Nusantara PGRI Kediri, 2023)
Research aim : The purpose of this study is to examine and analyze the effect of product quality, price, and service quality partially and simultaneously on customer repurchase intention at Marboba Outlet. Design/Methode/Approach : This study uses a quantitative approach and the technique used is causal associative. The population for this study were all customers who had purchased marboba products and the sample used in the study were 40 respondents who had repurchased and were analyzed using multiple linear regression methods. Research Finding : The results of this study are product quality, price, and service quality partially and simultaneously influence customer repurchase intention at Marboba Outlet. Theoretical contribution/Originality : - Practitionel/Policy implication : - Research limitation : The limitation of this research is the lack of time in sampling because it has entered the rainy season.